2013
DOI: 10.4172/2157-7536.1000136
|View full text |Cite
|
Sign up to set email alerts
|

Kaempferol Exhibits Progestogenic Effects in Ovariectomized Rats

Abstract: Objective Progesterone (P4) plays a central role in women's health. Synthetic progestins are used clinically in hormone replacement therapy (HRT), oral contraceptives, and for the treatment of endometriosis and infertility. Unfortunately, synthetic progestins are associated with side effects, including cardiovascular disease and breast cancer. Botanical dietary supplements are widely consumed for the alleviation of a variety of gynecological issues, but very few studies have characterized natural compounds in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 75 publications
(106 reference statements)
1
22
0
Order By: Relevance
“…This was a surprising finding, as previous studies found natural products that interacted with the PR had antagonist activity or no activity when tested in the presence of other PR ligands. 7,8,14,15 Only one other natural product study reported synergistic activity with steroid signaling. 16 In that study, extracts from Eucommia ulmoides synergistically increased androgen signaling, even in the presence of saturating concentrations of testosterone, but the compound responsible for this action was not isolated or further characterized.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a surprising finding, as previous studies found natural products that interacted with the PR had antagonist activity or no activity when tested in the presence of other PR ligands. 7,8,14,15 Only one other natural product study reported synergistic activity with steroid signaling. 16 In that study, extracts from Eucommia ulmoides synergistically increased androgen signaling, even in the presence of saturating concentrations of testosterone, but the compound responsible for this action was not isolated or further characterized.…”
Section: Resultsmentioning
confidence: 99%
“…6 We previously reported that the red clover constituent, kaempferol, exhibited progestogenic effects in ovariectomized rats, though its abundance and potency profile did not account for all of the progesterone activity observed in the crude extract. 7,8 This suggested that other progesterone-like compounds were present in red clover. In the current study, we employed a progesterone response element (PRE)-luciferase (Luc) reporter assay in Ishikawa cells to characterize the agonist and antagonist effects of red clover extracts, and to identify molecules responsible for the activity.…”
mentioning
confidence: 98%
“…Kaempferol (3,5,7-trihydroxy-2-(4-hydroxyphenyl)-4 H -1-benzopyran-4-one) is one of the flavonoids found in many edible plants, like tea, broccoli, cabbage, beans and tomato, and its name was derived due to its specific source of the rhizome of Kaempferi galangal L., known as a popular traditional aromatic plant [ 115 , 116 ]. As one of the phytoestrogens due to its polyphenolic structure, kaempferol also exerts anti-proliferative and anti-carcinogenic actions though ER, AR, the aryl hydrocarbon receptor (AhR) and the progesterone receptor (PR) signaling pathways in many types of cancer [ 117 , 118 , 119 ].…”
Section: Phytoestrogens and Their Actions On Cancer Cells Undergoimentioning
confidence: 99%
“…In the uterine stroma, genistein increased PR expression, as expected for an estrogenic compound. Interestingly, kaempferol did not reduce PR levels, as might be expected for a progestin (Toh et al, 2014). Kaempferol also increased amphiregulin A, a well-established progesterone stimulated gene.…”
Section: Phytoprogestinsmentioning
confidence: 56%
“…However, in the presence of progesterone, both compounds acted as antagonists, and reduced progesterone-stimulated PRE/luciferase activity by >50% (Toh et al, 2012). In a follow up study, kaempferol failed to induce ERE/luciferase or PSA/luciferase activity, showing its specificity toward PR (Toh et al, 2014). In vivo genistein (a phytoestrogen) increased proliferation of the uterine epithelium as measured by Ki67 immunostaining, and kaempferol reduced the effect.…”
Section: Phytoprogestinsmentioning
confidence: 99%